PENGARUH LINGKUNGAN KERJA DAN STRES KERJA TERHADAP KINERJA PEGAWAI PADA RUMAH SAKIT UMUM KOTA TANGERANG SELATAN - Rohilah, Dede; Priadi, Andri (Journal of Research and Publication Innovation, 2024)
This research aims to determine the influence of the work environment and work stress on employee performance at the South Tangerang City General Hospital partially or simultaneously. This research method is a quantitative method with a sample of 90 employees. The data collection methods used were questionnaires, observation, documentation and literature study. Data analysis techniques using statistical techniques include data instrument tests (validity test, reliability test), classical assumption tests (normality test, multicollinearity test, autocorrelation test, heteroscedasticity test), analysis tests (linear regression analysis, correlation coefficient analysis, coefficient of determination analysis) , and hypothesis testing (t test and f test). Data was processed using SPSS version 26.Based on the results obtained, the work environment has a significant effect on performance with the linear regression equation Y= 14.675 + 0.648 X1, the correlation coefficient value is 0.646, the determination value is 0.418,and the calculated t value > t table (7.947 > 1.987) and the significance value is 0.000. Job stress has a significant effect on performance with the linear regression equation Y= 23.899 + 0.461 X2, correlation coefficient value of 0.497,The determination value is 0.247, and the calculated t value > t table (5.369 > 1.987) and the significance value is 0.000.Simultaneously, the work environment and work stress variables have a significant effect on performance with a linear regression equation value of Y= 8.864 + 0.538X1 + 0.278X2, a correlation coefficient value of 0.704,The determination value is 0.496, with the results of the f test, the calculated f value > f table (42.772 > 3,10) and a significance value of 0.000.